THE TEACHING OF HISTORY IN RURAL SCHOOLS: PEDAGOGICAL PRACTICES IN THE INTERIOR OF THE AMAZON REGION OF PARÁ - Pedro dos Reis Costa, Jardel (Revista Gênero e Interdisciplinaridade, 2026)
History teaching has always been present in Brazilian primary schools since the arrival of the Jesuit priests, who were the first disseminators of formal education in Brazil. Throughout Brazil's political history, education, and in particular the teaching of History, has undergone different curricular changes, from narratives of the deeds of great politicians, in which facts appeared decontextualized, as if they were the work of a few individuals and not the result of collective construction, to the critical formation of subjects inserted in this educational dynamic about the processes of social transformation, providing them with conditions to construct their own interpretations and suggest ways of intervening in the society in which they live. Given these considerations, this article aims to analyze the pedagogical practice of three History teachers from the 1st to the 3rd year of high school at the João Paulo I State Elementary and High School, Boa Vista-Quatipuru, a rural school in the northeast of the state of Pará, in order to detect whether such practices associate the curricular content of History with local knowledge. The methodological approaches used to construct this work were: qualitative action research, bibliographic readings, and on-site observation of teaching practice, in addition to the construction of a teaching project as an intervention to recover the values ​​of the countryside based on the History content studied in the classroom. Upon completion of the research, it was found that teachers rarely connect curricular content with the sociocultural aspects of rural subjects; in other words, the educational paradigm adopted in the school in question is still urban-centric.